Penerapan Fungsi Manajemen Dalam Pengelolaan Perpustakaan di SMK Tamansiswa Padang - Sari, Winda; Marlini, Marlini (Ilmu Informasi Perpustakaan dan Kearsipan, 2012)
This paper focuses on the application of management functions in the management of the Library Tamansiswa SMK Padang. This study aims to reveal: (1) describe the application of management functions in the management of the library in the library Tamansiswa SMK Padang, (2) describe the implementation of activities in the management of library management functions in the library Tamansiswa SMK Padang, (3) describe the constraints in the implementation of management functions in the management of libraries in the library Tamansiswa SMK Padang. Based on the results of direct observation and interviews with library staff can be summarized as follows. First, the application management functions particularly in the processing of library materials in the library SMK Padang Tamansiswa not running optimally. Second, the activities in the application management functions particularly in the processing of library materials in the library Tamansiswa SMK Padang did not start well as penginventarisasian, classification and processing of library materials. Third, the absence of the constraints faced by human resources (HR) or personnel librarians who are experts in the library, in addition to the limited space in particular library reading room.